Oligoclonal M bands and cervical spinal cord lesions predict early secondary progressive multiple sclerosis - Alcalá Vicente, Carmen; Lacruz, Laura; Gascón, Francisco; Carratalà, Sara; Quintanilla-Bordás, Carlos; Sanz, Maria T.; Carcelén-Gadea, María; Mallada, Javier; Carreres, Joan; Gabaldón Torres, Laura; Dominguez, Jose Andres; Cañizares, Emmanuel; et al. (Frontiers in Neurology, 2022)
Objective To determine baseline cerebrospinal fluid and magnetic resonance imaging (MRI) variables at onset of clinically isolated syndrome (CIS) suggestive of multiple sclerosis (MS) that predict evolution to secondary progressive MS (SPMS). Methods 276 CIS patients with a minimum follow-up of 10 years were studied. Baseline presence of oligoclonal IgG and IgM bands (OCGB and OCMB respectively); number of brain T2 lesions (B-T2L), brain gadolinium enhancement lesions (brain-GEL), spinal cord T2 lesions (SC-T2L); and fulfillment of 2017 McDonald criteria among other variables were collected. Results 14 patients ended up with a non-MS condition. 138/276 CIS patients fulfilled 2017 McDonald criteria. Mean age was 32.4 years, 185 female. 227 received treatment, 95 as CIS. After a mean follow-up of 12 years, 36 patients developed SPMS. Conversion to SPMS was associated with OCGB (p=0.02), OCMB (p=0.0001); ≥ 9 B-T2L (p=0.03), brain-GEL (p=0.03), and SC-T2L (p=0.03). However, after adjusting for sex, age, BT2L, brain-GEL, SC-T2, and OCMB status, only OCMB (HR 4.4, 1.9-10.6) and SC-T2L (HR 2.2, 1.0-6.2) suggested an independent association with risk of conversion to SPMS. Patients with both risk factors had a HR of 6.12 (2.8-12.9). Discussion OCMB and SC-T2 lesions are potential independent predictors of conversion to SPMS.